An activated carbon fiber supported Fe2O3@bismuth carbonate heterojunction for enhanced visible light degradation of emerging pharmaceutical pollutants. Issue 11 (22nd September 2021) - Kar, Prasenjit; Shukla, Komal; Jain, Pratyush; Gupta, Raju Kumar
Abstract : The developed Fe2 O3 @BC heterojunction photocatalyst supported over activated carbon fiber exhibited efficient photocatalytic activity for degradation of antipyrine under visible light irradiation. Abstract : The development of broadband light-harvesting heterojunctions through interface tuning over flexible support has practical wastewater treatment applications. Immobilization of the heterojunction over flexible support such as activated carbon fiber (ACF) can prevent their elution in streamflow and make it versatile for its use in a reactor system. In this work, we report the development of a heterojunction by depositing iron(iii ) oxide nanoparticles over bismuth carbonate sheets supported over activated carbon fiber (Fe2 O3 @BC/ACF). The developed photocatalyst exhibits visible light photocatalytic activity towards the degradation of emerging pharmaceutical pollutants (antipyrine) under reactor operation. The higher photocatalytic activity (Fe2 O3 @BC/ACF1) has been explained in terms of interfacial tuning of the heterojunction and overall charge carrier separation upon different loading of Fe2 O3 nanoparticles on the BC surface. The key role of active radical species was studied during photocatalytic degradation of antipyrine. Intact crystallinity and no leaching of photocatalyst (Fe2 O3 @BC/ACF1) confirm the applicability of materials for future wastewater treatment applications.